Karakterisasi Morfologi dan Evaluasi Aksesi Lokal Alpukat Pulau Bangka: Karakterisasi Morfologi dan Evaluasi Aksesi Lokal Alpukat Pulau Bangka - Ihsan, Farihul; Hadori; Amellia (Universitas Bangka Belitung, 2024)
Avocado has not become a leading commodity in the Bangka Belitung Islands Province. The potential for avocado development in this region is still open because it is supported by local germplasm. Characterization and evaluation of local avocado germplasm need to be carried out to improve plants and obtain superior varieties. Research on morphological characterization and evaluation of local accession avocado fruit was conducted in the Bangka Island region from September 2021 to August 2022. Research was conducted on 4 avocado plants that were considered to have the potential superior accession, i.e., Babel-1, Babel-2, Babel-3 and Babel-4. Observations were made on the qualitative and quantitative characteristics of the fruit. The UPGMA hierarchical grouping method was used to analyze the similarity of accessions and scoring assessment method was used to assess its superiority. Based on observations of the morphological characteristics of the fruit, Babel-1 and Babel-2 avocados have a similarity coefficient of 67%, Babel-4 avocados 62%, and Babel-3 avocados 57%. The scoring assessment of the Babel-1, Babel-2, Babel-3, and Babel-4 avocados was: 72; 69; 64; 70.